2021
DOI: 10.1021/acs.jmedchem.1c01227
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Fusarium Graminearum Mitogen-Activated Protein Kinase (FgGpmk1) Inhibitor for the Treatment of Fusarium Head Blight

Abstract: Mitogen-activated protein kinase FgGpmk1 plays vital roles in the development and virulence of Fusarium graminearum (F. graminearum), the causative agent of Fusarium head blight (FHB). However, to date, the druggability of FgGpmk1 still needs verification, and small molecules targeting FgGpmk1 have never been reported. Here, we reported the discovery of a novel inhibitor 94 targeting FgGpmk1. First, a novel hit (compound 21) with an EC50 value of 13.01 μg·mL–1 against conidial germination of F. graminearum was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The optimal predicted binding mode of the ternary complex was then subjected to conventional molecular dynamics (MD) simulations. The 200 ns MD simulation protocol was similar to that previously reported . The calculation of RMSDs and extraction of representative structures of the simulated ternary complex was performed using the CPPTRAJ module in Amber 20 package .…”
Section: Methodsmentioning
confidence: 99%
“…The optimal predicted binding mode of the ternary complex was then subjected to conventional molecular dynamics (MD) simulations. The 200 ns MD simulation protocol was similar to that previously reported . The calculation of RMSDs and extraction of representative structures of the simulated ternary complex was performed using the CPPTRAJ module in Amber 20 package .…”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking is one of the most commonly used methods in structure-based drug design, which can predict the affinity between the ligand and the target; so, it can be used to screen bioactive compounds in the early stage of drug development. , Therefore, we chose BRAF inhibitor as an example to verify our mode. First, the crystal structure of the BRAF complex (PDB ID: 3OG7 and 6XFP ) was downloaded from the PDB database for simple optimization, including adding hydrogen atoms, distributing protonation state of residues, and minimizing the energy with the OPLS-2005 force field .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…This study provides ideas for the discovery of antifungals for Fusarium head blight management. 37 The role of MAPKs in being antifungal targets is so extensive that some potential fungicidal active substances have been reported. As is shown in Table 1, Liang et al suggested that the MAPK named PGPBS in Pyrenophora graminea, a phytopathogenic fungus, has pivotal roles in various biological processes, and its resistance to iprodione and tebuconazole has also been studied.…”
Section: Application Of Protein Kinases In Resistingmentioning
confidence: 99%
“…As is shown in Table , the EC 50 value of reported Compound 94 is 3.46 μg·mL –1 , and this compound may control the phosphorylation of FgGpmk1 and affect the nuclear localization of downriver FgSte12. This study provides ideas for the discovery of antifungals for Fusarium head blight management …”
Section: Protein Kinases As Potential Targets For Antifungalsmentioning
confidence: 99%